Implementation of Discovery Learning Methods to Improve Science Skills in Kindergarten B Children - Kevin William Andri Siahaan; Uci Nursanty Haloho; Maria Paulina Angle Raja Guk-guk; Fitri Riana Panjaitan (IKIP PGRI Bojonegoro, 2021)
AbstractThe implementation of science learning activities in Pematangsiantar City has not been optimal. Most of the teachers have not developed and used learning tools with the discovery learning method. The research objective was to determine the application of the discovery learning method to the science skills of kindergarten children through a scientific approach. The research method is quasi-experimental. To determine the effect of the application of the discovery learning method, learning was carried out in two classes, the experimental class and the control class. The results showed that there were differences in the value of science skills in the experimental class with the application of the discovery learning method with a comparison of the science skills scores of 24.64 before being given treatment and 29.92 after being given treatment. The application of discovery learning methods to science skills needs to be assisted and guided thoroughly. Keywords: discovery learning, science skills, kindergarten AbstrakPelaksanaan kegiatan pembelajaran IPA di Kota Pematangsiantar belum maksimal. Sebagian besar guru belum mengembangkan dan menggunakan perangkat pembelajaran dengan metode discovery learning. Tujuan penelitian untuk mengetahui penerapan metode discovery learning pada keterampilan IPA anak taman kanak-kanak melalui pendekatan saintifik. Metode penelitian adalah eksperimen semu. Untuk mengetahui pengaruh penerapan metode discovery learning ini, pembelajaran dilakukan di dua kelas, kelas eksperimen dan kelas kontrol. Hasil penelitian menunjukkan bahwa terdapat perbedaan nilai keterampilan IPA di kelas eksperimen dengan penerapan metode discovery learning dengan perbandingan nilai keterampilan IPA 24,64 sebelum diberikan perlakuan dan 29,92 setelah diberi perlakuan. Penerapan metode discovery learning pada keterampilan IPA perlu dibantu dan dibimbing secara menyeluruh. Kata Kunci :discovery learning,, keterampilan IPA, taman kanak-kanak